The effect of differentiated learning using geomath media on junior high school students’ mathematical concept understanding - Harahap, Dwi Fajri Hasanah; Azmi, Roma Doni; Dwinata, Alona (Pusat Studi Pengembangan Pembelajaran Matematika, 2026)
Understanding mathematical concepts (PKM) is an important thing that must be achieved by students to help them master the material more deeply, understand relationships between concepts, and prepare for more complex mathematical materials at the next level. Based on the findings from observations and interviews with mathematics teachers showed that students still lack understanding and apply mathematical concepts ineffectively. To overcome this problem, the researcher implemented differentiated learning with GeoMath media. The purpose of this research is to identify the effect of differentiated learning through the use of GeoMath media to enhance junior high school students’ understanding of mathematical concepts. The method was quasi-experimental with a quantitative approach. The research sample consisted of class IX.1 as the control group and class IX.3, which was assigned as the experimental group, selected through cluster sampling from all class IX students at SMP Negeri 1 Arse. The data collection was through a pretest and posttest, then analyzed using the independent sample t-test with a significance level of 5%. The results showed a significant value of 0,002. Since the test was a one-tailed test (right-tailed test), the sig. value =1/2 × 0,002 - 0,001, and since 0,001 <0,05, H0 is rejected and Ha is accepted, indicating a statistically significant difference between the posttest results of students in the experimental group and the control group. Thus, it can be concluded that the application of differentiated learning assisted by GeoMath media significantly improves students' understanding of mathematical concepts.